2021
DOI: 10.1186/s12913-020-05996-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that collaborative action between local health departments and nonprofit hospitals helps foster healthy behaviors in communities: a multilevel study

Abstract: Background The Patient Protection and Affordable Care Act of 2010 (ACA) encouraged nonprofit hospitals to collaborate with local public health experts in the conduct of community health needs assessments (CHNAs) for the larger goal of improving community health. Yet, little is known about whether collaborations between local health departments and hospitals may be beneficial to community health. In this study, we investigated whether individuals residing in communities with stronger collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(50 citation statements)
references
References 11 publications
1
49
0
Order By: Relevance
“…The patients in the P4P group had an average of two more physician visits for diabetes than those in the comparison group. Wu et al [ 38 ] reported that participation in the P4P program might have reduced the risk of ER infection events and resulted in lower infection-related deaths in patients with type 2 diabetes. Despite the previous demonstration of the benefits of P4P participation for patients with diabetes in reducing the risk of death [ 14 , 37 ], there has been no report including BMI as a variable.…”
Section: Discussionmentioning
confidence: 99%
“…The patients in the P4P group had an average of two more physician visits for diabetes than those in the comparison group. Wu et al [ 38 ] reported that participation in the P4P program might have reduced the risk of ER infection events and resulted in lower infection-related deaths in patients with type 2 diabetes. Despite the previous demonstration of the benefits of P4P participation for patients with diabetes in reducing the risk of death [ 14 , 37 ], there has been no report including BMI as a variable.…”
Section: Discussionmentioning
confidence: 99%
“…Informal caregiving, which is defined as the unpaid care provided to dependent relatives or family members [ 42 ], seems to increase even more the psychological consequences of the COVID-19 pandemic. Greater levels of anxiety, depression and even somatic symptoms have been found in this population [ 40 , 43 , 44 , 45 , 46 ], while its caregiving intensity and burden increased during this period [ 47 , 48 ]. Due to the complete closure of day-care centers, the loss of support services and the saturation of healthcare capacities, informal caregivers had played an even more important role during COVID-19 pandemic [ 43 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Greater levels of anxiety, depression and even somatic symptoms have been found in this population [ 40 , 43 , 44 , 45 , 46 ], while its caregiving intensity and burden increased during this period [ 47 , 48 ]. Due to the complete closure of day-care centers, the loss of support services and the saturation of healthcare capacities, informal caregivers had played an even more important role during COVID-19 pandemic [ 43 , 49 , 50 ]. For this reason, informal care has been considered an additional stressor that can negatively affect the physical and mental health of an already vulnerable population [ 43 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To efficiently serve the needy and achieve the mission of helping to improve their health, charitable organizations, for example, must coordinate and collaborate with counties, governorates, welfare organizations and relief councils, and medical universities. However, in the Iranian health system, such a partnership between these institutions has yet to be established [ 15 ].…”
Section: Introductionmentioning
confidence: 99%